EKSPLORASI SAINS ILMIAH PADA PEMBUATAN DODOL TRADISIONAL KHAS DESA PENGLATAN UNTUK MENDUKUNG PEMBELAJARAN IPA SMP - Luh Nia Rismayanti; Putri Sarini; Kompyang Selamet (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The process of making Penglatan Village's signature dodol has been widely understood from an economic and social perspective, while the scientific potential inherent in the manufacturing process has not been extensively studied. This study aims to explore the scientific concepts contained in the process of making Penglatan Village's signature dodol as a supporting context for science education. This research is a descriptive qualitative study through data reduction, data presentation, and conclusion drawing using an ethnoscience approach. The research subjects were producers of Penglatan dodol. Data collection was conducted using observation and interview techniques. Source triangulation, technique triangulation, and member checking were used to improve data credibility by testing data validity. The results showed that the stages of stirring dodol, melting brown sugar, using old coconut milk, additives, and the dodol cooking process represent scientific concepts, such as heat transfer, the role of fat in heat conduction and starch gelatinization, additives, motion systems, and exothermic reactions. These findings are relevant to junior high school science learning in the context of changes in substance properties, additives, heat and combustion reactions, motion and force, mixture separation, and environmental pollution. The results of this study contribute to strengthening the integration of local contexts through scientific exploration in the making of dodol, a specialty of Penglatan Village, as a support for learner development.